PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS III SD NEGERI 101822 PANCUR BATU - Monasari Marbun, Elvina; Patri Janson Silaban; Darinda Sofia Tanjung; Frikson Jony Purba; Eka Kartika Silalahi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Cooperative Learning model of the Index Card Match type on student learning outcomes in Mathematics for Grade III at SD Negeri 101822 Pancur Batu in the 2024/2025 academic year. This research uses a quantitative approach with a One Group Pretest-Posttest Design. The subjects of this study were all 21 students of the third grade. The instruments used included tests and questionnaires. The test was administered in the form of a pre-test and post-test, each consisting of 20 questions, to measure the improvement in learning outcomes before and after the implementation of the learning model. The pre-test results showed an average score of 54, with only 6 students (29%) achieving the Minimum Mastery Criteria (KKTP). After the implementation of the Cooperative Learning model of the Index Card Match type, the post-test results improved, with an average score of 77, and 17 students (81%) achieving mastery. The normality test results showed that the data were normally distributed. The correlation test produced an r-value of 0.933 ≥ t-table value of 0.433, indicating a very strong relationship. The t-test showed a t-count of 11.294 ≥ t-table of 2.093, thus Ha was accepted. The results of the study prove that the Cooperative Learning model of the Index Card Match type has a significant and effective impact on improving student learning outcomes. This model is able to create an active, enjoyable learning environment that directly engages students in understanding the concept of simple fractions.